Investigating Spectrum Allocation Policies to Accommodate New Entrants in the Market: A Case Study of South Africa - Xulu, Khanyisani Khayelihle; Malatji, Masike (International Journal of Membrane Science and Technology, 2023)
One of the goals of the telecommunications industry is to provide universal connectivity to its consumers. Achieving this goal is highly dependent on the allocation of radio frequency (RF) spectrum. The RF spectrum refers to the frequencies assigned to diverse services such as mobile, fixed, and satellite services. These allocations are regulated by international, regional, and local authorities. Countries across the globe have embarked on the journey to transform their RF spectrum allocation policies to be more inclusive and hybrid in nature. Such changes in some countries, have enabled new entrants and incumbent operators to provide low-cost connectivity into small rural communities, bridging the digital divide gap. Due to current policies by some regulators and perceived anti-competitive laws, new entrants and small operators find it difficult to penetrate the telecommunications market in South Africa. To address this challenge, the overall and ongoing study, proposes an alternative and inclusive framework for universal coverage and low-cost connectivity that accommodates both incumbent and new entrant operators in South Africa. To achieve this aim, a qualitative desktop research approach was used to analyze publicly available information, including journal articles, RF spectrum policy documents from various countries, International Telecommunication Union (ITU) documents and other academic sources. The objective of this paper is to contribute to the ongoing discussions regarding the policy on the allocation of RF spectrum. As this is an ongoing study, preliminary findings indicated that auctions remain a popular RF spectrum allocation model of choice, despite being perceived by some scholars as less competitive and inflexible. The final study findings, which would be in a subsequent research paper, aim to develop a new RF spectrum framework that may help achieve universal coverage and low-cost connectivity in South Africa.